Kis- és középvállalkozások adózási módjai – egy könyvelőiroda szemszögéből - Szarka Katalin Márta (2016)
In my thesis I would like to present the taxation methods of small and medium enterprises from an accounting office's perspective and also the entrepreneurs and companies by the type of their business management. The number of operating ventures has slightly but continuously decreased in the last 5 years, although the number of taxes applying to them has gradually increased. I start my thesis with introducing the place of my exercise, an accounting centre called “2 Németh Könyvelőcentrum”, then continue with the presentation of the accounting office and the used computer programs. After this I describe the rules of foundation, operation and dissolution of individual proprietorships and joint ventures. Then I expound the taxation rules separately for entrepreneurs first comparing the ratio of the chosen tax types to the national average, then presenting the rules for the most important taxes. After that, I would like to show the most important taxation rules for joint ventures and the way of choosing the taxes with comparative tables. Following this I present the common rules for individual entrepreneurs and companies, later I describe the different regulations with respect to the most frequently occurring types of taxes in the accounting office such as value added tax, simplified entrepreneurial tax, company car tax, and food chain supervision fee. It can be concluded that both individual entrepreneurs and corporate businesses pay the same rate of tax. This amount is 10 percent of the positive tax base, it is called personal income tax in case of private enterprises and corporate tax in case of joint ventures, for dividend tax 15 percent personal income tax and 14 percent healthcare contribution tax should be payed. A difference is that individual businesses should pay the personal income tax quarterly in advance in the current year, based on the actual result, while the companies are required to pay the corporate advance tax quarterly afterwards, based on their tax liabilities in the earlier years. Also, it is mandatory for the entrepreneurs to pay the dividend and remove it from the venture. Final conclusion is that the ventures should examine their enterprises from legal, accounting, tax and business management aspects, be them individual or corporate ones. This examination can happen together with the accountant, or even with the attorney of the company to solve the problem. Therefore, it is not enough if the venture turns to an adequte accountant professional, but a legally qualified person is also needed to inspect the ever-changing legal background.